Adsorptive Removal of Atrazine From Contaminated Water Using Low-Cost Carbonaceous Materials: A Review - Ahmad, Munir; Riaz, Umair; Iqbal, Shazia; Ahmad, Jahangir; Rasheed, Hina; Al-Farraj, Abdullah S. F.; Al-Wabel, Mohammad I. (Frontiers in Materials, 2022)
Extensive utilization of atrazine (estimated consumption of 70,000–90,000 tons per annum globally) to eliminate undesirable weeds has resulted in the accumulation of atrazine and its metabolites (diaminochlorotriazine, deisopropylatrazine, desethylatrazine, and atrazine mercapturate) in surface and groundwater above maximum permissible limits (drinking water: 3 μg L−1 in the United States, 0.1 μg L−1 in Europe, and 3.0 μg L−1 by the WHO). Atrazine exhibited no to low degradation in aquatic environments; however, poor degradation in soil yields toxic metabolites, which serve as sinks for groundwater resources. Due to mobility, atrazine and its metabolites can persist in various environmental matrices for decades without degradation, posing a serious threat to ecosystem sustainability and, thus, being removed from water resources. Majority of conventional wastewater treatment technologies are either expensive or inefficient. The carbonaceous materials such as activated carbon, biochar, carbon nanotubes, and graphene have been employed as potent adsorbents for the efficient removal of atrazine along with its metabolites from wastewater. Thus, the efficacy of the aforementioned carbonaceous adsorbents for atrazine removal has been discussed in this article by reviewing 161 published articles. The literature survey demonstrated the highest atrazine adsorption capacity of activated carbons (13.95–712.10 mg g−1), followed by biochar (4.55–409.84 mg g−1) and carbon nanotubes (28.21–110.80 mg g−1). Atrazine adsorption onto the carbonaceous adsorbents is a complex process involving single or multiple mechanisms, such as hydrogen bonding, electrostatic interactions, van der Waals forces, hydrophobic interactions, π-π electron donor–acceptor interactions, pore filling, and partitioning. It is recommended that monitoring of atrazine and its metabolites in water resources and their impacts on human and animal lives be explored. Furthermore, modification of carbon-based adsorbents with chemical, mechanical, and thermal means, as well as development of hybrid systems, may completely remove the prevailing atrazine and its metabolites from world water resources.